2021
DOI: 10.3390/brainsci11020199
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Location of the Vestibulocerebellar Tract in the Healthy Human Brain: A Diffusion Tensor Imaging Study

Abstract: The vestibulocerebellar tract (VCT) is regarded as an important pathway of the central vestibular system. We identified the anatomical characteristics of the primary and secondary VCTs in a normal human brain using diffusion tensor imaging (DTI) tractography. Thirty-one healthy adults were recruited. A 1.5 T scanner was used for DTI tractography. A seed region of interest (ROI) was placed on the superior and medial vestibular nuclei at the pons level and a target ROI was placed on the uvula–nodulus of the cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…They found that these EPs of potential cerebellar origin were larger on the right side for bone conducted sounds ( 108 ), an observation not confirmed with stronger vestibular stimulation ( 41 ). Secondary vestibular fibers project bilaterally to the cerebellum in both animals and humans ( 17 , 192 , 193 ). However, unlike in humans, animal studies converge on larger contralateral responses to vestibular stimulation in the vermis and flocculus ( 194 ).…”
Section: Discussionmentioning
confidence: 99%
“…They found that these EPs of potential cerebellar origin were larger on the right side for bone conducted sounds ( 108 ), an observation not confirmed with stronger vestibular stimulation ( 41 ). Secondary vestibular fibers project bilaterally to the cerebellum in both animals and humans ( 17 , 192 , 193 ). However, unlike in humans, animal studies converge on larger contralateral responses to vestibular stimulation in the vermis and flocculus ( 194 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of research comparing hand function using the Purdue pegboard test with the specific regions and neural pathways of cerebellum. The vestibulocerebellar tract (VCT) is a neural pathway that connects the vestibular nucleus to the uvula nodulus of the cerebellum, and is responsible for maintaining balance, spatial orientation, and coordination [21]. In general, the vestibular system detects changes in head position and movement, and controls static and dynamic balance based on vestibular sensory information [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The vestibulocerebellar tract (VCT) is a neural pathway that connects the vestibular nucleus to the uvula nodulus of the cerebellum, and is responsible for maintaining balance, spatial orientation, and coordination [21]. In general, the vestibular system detects changes in head position and movement, and controls static and dynamic balance based on vestibular sensory information [21,22]. Damage to the vestibular system is accompanied by an impairment of the sense of position and movement, and symptoms of balance disorder or ataxia [23][24][25].…”
Section: Introductionmentioning
confidence: 99%